Evaluation of the Antibacterial Activity of Quercus persica Jaub & Spach Fruit's Hidroalcoholic Extract in Disc Diffusion Method - A Ebrahimi; M Khayami; V Nejati (Institue of Medicinal Plants, ACECR, 2010)
Background: As a result of indiscriminate use of antimicrobial drugs in the treatment of infectious diseases, microorganisms have developed resisrtance to many antibiotics and there is a need to develop antimicrobial drugs. One approach is use of local medicinal plants which represent a rich source of novel antimicrobial agents. Objective: Due to rapid increase of antibiotics resistance, fewer side effects of chemical drugs, antibacterial properties of oaks and other reasons, this study was carried out. Methods: In this study the antibacterial activity of hidroalcoholic extract of oak fruit was evaluated and compared with some in - use antibiotics. Milled oak fruit that their hull was separated was extracted with water+ethanol in Soxhleťs apparatus .The effect of extract in three concentration (25, 50, 75 mg/ml) were tested using agar diffusion method on Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis RTCC 1898 and Escherichia coli O157: H7. Results: Results showed that the effect of the extract on bacteria was concentration-dependent. In compared with antibiotics, the effect of 75 mg/ml concentration of extract on S. aureus was similar to GM, lesser than K and higher than TOB. Also this concentration of extract had a similar effect to K, higher than GM and lesser than TOB on S. epidermidis. This effect on E. coli was lesser than GM and K, but in compared with TOB was higher. Conclusion: results show that Quercus persica J. & Sp. possesses compounds with antibacterial properties.